Pengaruh Self-compassion Therapy terhadap Tingkat Depresi Pasien Diabetes Melitus - I Gusti Ayu Harini; Putu Yoan Sugiantara; I Wayan Candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2021)
People with Diabetes Mellitus (DM) have a higher risk of developing depression. To treat depression in patients with DM, non-pharmacological therapies such as self-compassion therapy are needed. The aims of research to determine effect self-compassion therapy to depression levels diabetes mellitus patients in Work Area of Puskesmas I Denpasar Barat on 2021. This research used the method pre-experimental with one-group pre-post test design. Sampling with non-probability sampling with purposive sampling. Respondents were 17 people. The research instrument used Beck Depression Inventory-II. The normality test uses Shapiro-Wilk test. Hypothesis testing using Wilcoxon Signed Ranks Test. The results showed that most respondents were in mild depression category 10 peoples (58.8%), the rest were moderate depression (41.2%) before being given self-compassion therapy. After treatment level of depression decreased, 3 people had moderate depression (17.6%), 9 people had mild depression (52.9%), and least 5 people not depression (29.4%). After analysis, p-value was obtained at Sig. (2-tailed) = 0.000 alpha (0.05). The conclusion was that there is an effect of self-compassion therapy to depression levels on diabetes mellitus patients in Work Area Puskesmas I Denpasar Barat on 2021, meaning reduce depression levels Therefore, it is hoped that self-compassion therapy can be applied to patients with DM who experience depression.